2017
DOI: 10.1017/s1368980017002889
|View full text |Cite
|
Sign up to set email alerts
|

Can existing mobile apps support healthier food purchasing behaviour? Content analysis of nutrition content, behaviour change theory and user quality integration

Abstract: Existing mobile apps may offer a potentially effective approach to supporting healthier food purchasing behaviour but improvements in mobile app design are required to maximise their potential effectiveness. Engagement of mobile app users and nutrition professionals is recommended to support effective design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 71 publications
3
77
0
Order By: Relevance
“…First, all efforts need to be part of an integrated approach in order to be optimally effective (Stern, 2000). Berger (2019) found that an approach that combines gamification elements with norm-based feedback (especially feedback based on injunctive norms) effectively steers consumers toward more sustainable food choices. Yokessa and Marette (2019) conclude that it is usually best to combine eco-labeling with other regulatory tools such as standards banning polluting products and including tax mechanisms.…”
Section: Further Considerationsmentioning
confidence: 99%
“…First, all efforts need to be part of an integrated approach in order to be optimally effective (Stern, 2000). Berger (2019) found that an approach that combines gamification elements with norm-based feedback (especially feedback based on injunctive norms) effectively steers consumers toward more sustainable food choices. Yokessa and Marette (2019) conclude that it is usually best to combine eco-labeling with other regulatory tools such as standards banning polluting products and including tax mechanisms.…”
Section: Further Considerationsmentioning
confidence: 99%
“…However, the small number of studies identified, and wide range of outcomes evaluated limited conclusions which could be drawn. User engagement, which is an important determinant of intervention effectiveness [26,66], was seen to be a challenge in evaluated studies. Similarly, many websites and apps identified in objective three scored poorly for engagement.…”
Section: Discussionmentioning
confidence: 99%
“…The medical and public health literature includes studies on nutrition, diabetes management, calorie-counting, or weight-loss apps. Several of these studies have focused on features of food-tracking apps' content such as their accuracy, usability, and accountability [25]; whether they conform to evidence-informed practices [26] or incorporate expert medical or nutritional knowledge [27,28]; or psychological models of behaviour [29]. Another group of studies has directed attention to how food-tracking apps are used, focusing on elements such as whether they contribute to eating disorders [30,31], and their efficacy in weight-loss efforts [32] and diabetes management [33].…”
Section: Previous Research On Food-tracking Appsmentioning
confidence: 99%